Profile of Organs in Broiler Given Tourism Powder, Garlic,and Zink Mineralas Feed Additional - Fuji Astuty Auza; Rusli Badaruddin; Hairil A. Hadini; Wa Laili Salido; La Ode Munadi (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2022)
The aim of this study was to examine the effect of giving turmeric (3%), garlic (5%) and zinc minerals (180 ppm) to the internal organ weight of broilers. The study used 100 DOC broilers, Strain Arbor Acres 707, divided into 5 treatments and 4 replications, each treatment consisting of 5 birds. The data obtained were statistically analyzed using a Completely Randomized Design (CRD) and further tested for orthogonal contrast. The treatment rations were R0 (finished ration or control), R1 (finished ration + 5% garlic powder + 3% turmeric powder, R2 (finished ration + 5% garlic powder + 180 ppm ZnO), R3 (finished ration + turmeric powder 3 % + ZnO 180 ppm), R4 (finished ration + 5% garlic powder + 3% turmeric powder + ZnO 180 ppm).The results showed that the administration of garlic powder, turmeric and zinc minerals did not show a significant effect (P>0,05) to the relative weight of internal organs.The R1 treatment with a combination of garlic powder (5%), turmeric powder (3%) tends to increase the percentage of heart and pancreas organ weights, while the R4 treatment with a combination of garlic powder (5%), turmeric powder (3%) and ZnO 180 ppm tend to increase the percentage of liver weight.